Pengaruh Lingkungan Sosial Terhadap Pola Komunikasi Remaja di Perkotaan:: Studi Kualitatif Pada Remaja Dikota Bandung - Almadina Rakhmaniar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to explore the influence of the social environment on the communication patterns of adolescents in urban areas. A qualitative approach is used to understand how factors such as family, peers, school environment, social media, local culture, socioeconomic status, globalization, and physical environment influence the way adolescents communicate. Data were collected through in-depth interviews, participatory observation, focus group discussions and case studies. The respondents in this study were 100 respondents from teenagers in Bandung city.The results showed that family has a central role in shaping adolescents' communication skills, with supportive parenting increasing openness and communication effectiveness. Peers also have a significant influence, where adolescents adjust their communication style to gain social acceptance. School environments that support open and participatory communication have been shown to improve adolescents' communication skills, while the use of social media and modern technology changes the mode and frequency of communication, although sometimes reducing face-to-face interactions.Local culture and urbanization introduce adolescents to more modern and dynamic communication styles, while socioeconomic status affects access to education and technology, which in turn affects communication skills. Globalization and exposure to foreign cultures broaden adolescents' communication horizons, allowing interaction with various groups. Finally, the urban physical environment, including public facilities and population density, affects adolescents' interaction and communication patterns. The findings provide implications for policies and interventions aimed at improving adolescents' communication skills through a holistic approach involving family, school, community, and management of social media use.